Incorporating inflammatory biomarkers into a prognostic risk score in patients with non-ischemic heart failure: a machine learning approach - Feng, Jiayu; Zhao, Xuemei; Huang, Boping; Huang, Liyan; Wu, Yihang; Wang, Jing; Guan, Jingyuan; Li, Xinqing; Zhang, Yuhui; Zhang, Jian (Frontiers in Immunology, 2023)
Inflammation is involved in the mechanisms of non-ischemic heart failure (NIHF). We aimed to investigate the prognostic value of 21 inflammatory biomarkers and construct a biomarker risk score to improve risk prediction for patients with NIHF.Methods: Patients diagnosed with NIHF without infection during hospitalization were included. The primary outcome was defined as all-cause mortality and heart transplantations. We used elastic net Cox regression with cross-validation to select inflammatory biomarkers and construct the best biomarker risk score model. Discrimination, calibration and reclassification were evaluated to assess the predictive value of the biomarker risk score.Of 1250 patients included (median age 53 years, 31.9% female), 436 patients (34.9%) experienced the primary outcome during a median of 2.8 years of follow-up. The final biomarker risk score included high-sensitivity C-reactive protein-to-albumin ratio (CAR) and red blood cell distribution width-standard deviation (RDW-SD), both of which were 100% selected in 1000 times cross-validation folds. Incorporating the biomarker risk score into the best basic model improved the discrimination (∆C-index=0.012, 95% CI 0.003-0.018) and reclassification (IDI, 2.3%, 95% CI 0.7%-4.9%; NRI, 17.3% 95% CI 6.4%-32.3%) in risk identification. In the cross-validation sets, the mean time-dependent AUC ranged from 0.670 to 0.724 for the biomarker risk score and 0.705 to 0.804 for the basic model with a biomarker risk score, from 1 to 8 years. In multivariable Cox regression, the biomarker risk score was independently associated with the outcome in patients with NIHF (HR 1.76, 95% CI 1.49-2.08, P<0.001, per 1 score increase).Conclusions: An inflammatory biomarkers-derived risk score significantly improved prognosis prediction and risk stratification, providing potential individualized therapeutic targets for NIHF patients.